In vitro digestion and cellular antioxidant activity of β-carotene-loaded emulsion stabilized by soy protein isolate-Pleurotus eryngii polysaccharide conjugates. (March 2021) - Hu, Qiuhui; Wu, Yiliang; Zhong, Lei; Ma, Ning; Zhao, Liyan; Ma, Gaoxing; Cheng, Ninghui; Nakata, Paul A.; Xu, Juan
Abstract: β-Carotene is a natural fat-soluble antioxidant, while the poor oral bioavailability of β-carotene restricts its application for functional foods. To overcome this barrier, a stable oil-in-water emulsion was structured to effectively deliver β-carotene. In this study, soy protein isolate (SPI)-Pleurotus eryngii polysaccharide (PEP) conjugate was prepared by Maillard reaction under controlled wet-heating conditions. β-Carotene was encapsulated in SPI-PEP conjugate-stabilized emulsion and its gastrointestinal behavior and antioxidant activity were assessed in vitro. The results showed that such conjugate with high molecular weight was mainly formed through PEP covalently binding to lysine and cysteine of SPI via C–N. Changes in spatial structure of SPI-PEP conjugate resulted from its decreased tryptophan fluorescence intensity and unfolded protein secondary structure. A decreased surface hydrophobicity and flat surface morphology of SPI-PEP conjugate contributed to its increased water solubility and emulsibility. Additionally, lipid digestion and the formation of mixed micelles were promoted in SPI-PEP conjugate-stabilized emulsion due to its strong steric repulsion, resulting in an improved bioavailability of β-carotene. Such improvement was favorable for β-carotene to relieve tert-butyl hydroperoxide-induced oxidative stress by decreasing reactive oxygen species production and enhancing antioxidant enzyme activities in Caco-2 cells. Our study suggested that Maillard-type protein-polysaccharide conjugates-stabilized emulsions had a potential industry application for the delivery of fat-soluble nutrients. Graphical abstract: Image 1 Highlights: SPI-PEP Maillard conjugate was prepared under controlled wet-heating conditions. Structural changes of conjugate promoted its water solubility and emulsibility. Conjugate emulsion improved the bioavailability and antioxidation of β-carotene.